Pengaruh Kemampuan Komunikasi Guru terhadap Minat Belajar Siswa Kelas XI SMK NU Ungaran - Musanan, Muhamad Habsi; Karim, Abdul; Rinenggo, Alil (Faculty of Teacher Training and Education of Undaris, 2024)
This research is motivated by the delivery of material from PPKn teachers which tends to be monotonous and lacks variety, as well as indicators of teacher communication skills not being optimal according to Yosal Iriantara (2013:7), such as being able to ask questions that encourage students to understand the learning material themselves, being able to ask questions that encourage questions. high level, and skilled in various interaction techniques to prevent boredom. The formulation of the problem in this research is whether there is a significant influence between teachers' communication skills on the learning interest of class.This research is quantitative. The subjects of this research were class The sampling technique applied was cluster proportional random sampling. Data collection techniques use questionnaires, data analysis uses normality tests, regression tests, determination tests and F tests with the help of the SPSS 22 program. The results of the research state that there is a significant influence between teachers' communication skills on interest in learning Civics in class 5%. Based on the results of the research that has been carried out, it can be concluded that each variable is related.Keywords: Teacher Communication Ability, and Student Learning Interest